CBCT Evaluation of Condylar Changes in Class II Hyperdivergent Adult Patients Following Posterior Maxillary Intrusion Using Miniscrews/Miniplates—A Prospective Study. Issue 2 (April 2020) - Bajaj, Kamal; Rathee, Pooja; Goyal, Deepak
Abstract: Aim & Objectives: To evaluate using CBCT, the condylar changes taking place in retrognathic, hyperdivergent Class II adult patients following maxillary intrusion using miniscrew assembly. Materials and methods: In this prospective study design, 20 class II div I high angle cases in the age group of 20-25 years with Class II molar and canine relationship; Overjet > 5mm; ANB angle > 4°; FMA angle >25°; SNGoGn > 35°; Jaraback ratio< 60° and Lower Gonial angle>75° were taken. Each patient had a miniscrew assembly in the maxilla through which intrusive force was applied to the maxilla. Two additional miniscrews were placed between the first mandibular molars and second premolars to prevent extrusion of lower molars. CBCT images were taken at the beginning of the treatment (T1) and at the end of 6-9 months of molar intrusion (T2). Statistical analysis was carried out using student T- test. Results: Prior to treatment, the patients showed significant mandibular retrusion associated with increased maxillary posterior heights. Following maxillary intrusion with miniscrew assembly, CBCT evaluation revealed that the distance from the centre of condyle to the posterior border of the external auditory meatus was 19.2±1.67 mm on right side and 18.1±1.54mm on left side in T1 which increased to 19.6±1.45mm on right side and 18.5±1.36mm on left side in T2. The average forward displacement of condyle was .5mm which was statistically significant. The distance from the centre of condyle to superior border of external acoustic meatus was 3.1±1.7 mm on right side and 3.5 ±1.8 mm on left side in T 1 which increased to 3.8±1.9 mm on right side and 4.1 ±1.3mm on left side in T 2. The average downward displacement was .7mm which was statistically significant. Conclusion: Significant Maxillary intrusion can be achieved using miniscrews/ miniplate in adult hyperdivergent skeletal class II patients.